2001
DOI: 10.4049/jimmunol.167.9.4974
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 Has a Direct Effect on Naive CD4+ T Cells to Enhance the Development of Th2 Cells

Abstract: 1α,25-Dihydroxyvitamin D3 (vitD3) is an immunoregulatory hormone with beneficial effects on Th1 mediated autoimmune diseases. Although the inhibitory effects of vitD3 on macrophages and dendritic cells are well documented, any direct effects of vitD3 on Th cell development are not clearly defined. Using CD4+Mel14+ T cells derived from mice on a BALB/c and a C57BL/6 genetic background we examined the effect of vitD3 on Th cell development. We demonstrated that vitD3 affects Th cell polarization by inhibiting Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
706
6
18

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,047 publications
(772 citation statements)
references
References 52 publications
21
706
6
18
Order By: Relevance
“…62 Indeed, it has been suggested that some, at least, of the immunosuppressive effects of sun exposure may be mediated by vitamin D production. 63 Therefore, more research is required before we can be at all certain that vitamin D synthesis mediates a protective effect of sun exposure against NHL, if there is one.…”
Section: Resultsmentioning
confidence: 99%
“…62 Indeed, it has been suggested that some, at least, of the immunosuppressive effects of sun exposure may be mediated by vitamin D production. 63 Therefore, more research is required before we can be at all certain that vitamin D synthesis mediates a protective effect of sun exposure against NHL, if there is one.…”
Section: Resultsmentioning
confidence: 99%
“…GATA-3 is an important transcription factor directing the polarisation of naïve T cells to Th-2 cells (Rengarajan et al, 2000). 1a,25-dihydroxyvitamin D 3 has been shown to upregulate GATA-3 gene expression and the GATA-3 protein promotes polarisation to Th-2 (Boonstra et al, 2001). The present findings would suggest that the GATA-3 response element in the A allele of the VDR promoter may produce a positive feedback loop and amplify the GATA-3-induced polarisation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded in 24-well TC plates coated with 10 mg ml À1 of anti-CD3 and 6 mg ml À1 of anti-CD28 antibodies, and cultured at the concentration of 2 Â 10 6 cells per ml in the presence of 10 ng ml À1 of human IL-2 for 5 days. 50 All recombinant cytokines used in experiments were purchased from PeproTech (Rocky Hill, NJ, USA). The purity of CD4 þ CD62 L þ T cells before TCR stimulation was about Figure 5 The nAChR subunits and mAChR subtypes expressed in Th1, Th2 and Th17 cells.…”
Section: Tcr Stimulationmentioning
confidence: 99%